THU0139 Cardiovascular Risk Factor Profile in an Italian Cohort of Patients with Rheumatoid Arthritis: Results of a Three Year Follow-up. (9th June 2015) - Grosso, G.; Erba, G.; Valena, C.A.; Riva, M.; Betelli, M.; Allevi, E.; Bonomi, F.; Barbarossa, S.; Ricci, M.; Facchetti, R.L.; Pozzi, M.R.; Grassi, G.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease characterized by an elevated cardiovascular morbidity and mortality, but detailed information on the risk score profile using different approaches, as well as on the major determinant(s) of the cardiovascular risk of these patients are scanty. Objectives: The present study reports data collected in a cohort of RA patients with CV risk score calculators Framingham and SCORE uncorrected or corrected according to EULAR recommendations. Cardiovascular events were recorded during the 3 year follow-up, to determine the burden of CV morbidity and the relative impact of traditional CV risk factors and disease activity/severity. Methods: We enrolled 198 pts. We use Framingham and SCORE to predict CV risk. Cardiovascular events were recorded during the 3 year follow-up. Results: We enrolled 198 pts, 77% females, age 65.0±11.6 yrs (means ± SD), disease duration 13±9 yrs. 76% of pts were RF +, 68% ACPA+ and 46% with erosive disease. The mean DAS28 CRP was 2.67±1.17. 3% were smokers and 32% ex smokers. Mean BMI (24.6±44), plasma levels of cholesterol (total, HDL, LDL), triglycerides and glucose and prevalence of smokers were comparable with those detected in the local general population (GP), while the prevalence of hypertension (78 and 71% in RA M/F vs 49 and 43% in GP M/F) and diabetes (21.7 and 10.8% in RA M/F vs 4.8 and 2, 58% in GP M/F) were significantly higher in both male and females. Risk scores with Framingham were lower than in GP and comparable using SCORE, but the application of 1.5x correction factor for RA, as recommended by EULAR, modified these figures. The number of hypertensive and diabetic pts increased significantly (P<0.0001/0.019) during the follow-up as well as the mean values of Framingham and SCORE (p<0.015/0.011). The MI and stroke prevalence were 5% and 2% respectively: the incidence rate/1000 person/year were 8.8 and 3.7 versus 2.7 and 2.6 in the general population. No relation was detectable between disease activity indices and CV events or risk scores. Half of our patients were treated with Prednisone ≤7.5 mg/day: lipid profile, glucose level and blood pressure were comparable in steroid-treated and steroid-free patients. Conclusions: The present study provides evidence that 1) RA is associated with an increased CV morbidity even in the medium follow-up period, 2) risk score needs to be adjusted as by EULAR indications to obtain sensitive assessment of risk 3) that hypertension represents a major CV risk factor in this population and 4) that the achievement of low disease activity doesn't seem sufficient to reduce the CV risk. Disclosure of Interest: None declared